Resilience of traditional midwifery in Southern Cameroons: 1922-1961 - Lueong, Nina-Prazil LIENJEH; Ngwa, Canute A. (International Journal of Scientific Research and Management (IJSRM), 2023)
It is instructive that well organized healthcare systems existed in Africa before contacts with the outside world. During this period, midwifery services were prioritized because societal wellbeing depended on the quality and availability of child and maternity services. The arrival of European colonial imperialists with their assumed superior culture/civilization and their colonial economic agenda caused the introduction of Western biomedicine. This was intended in part to maintain a constant and healthy work force for colonial exploitation. Drawing from the case of Southern Cameroons, this paper sets out to examine the resilience of local midwifery practices in the face of an imposed Western biomedicine. The paper was informed by both primary and secondary sources. Archival information and oral interviews made up the primary sources while books, published articles and dissertations constituted the secondary sources. The discriptive historical approach was employed in the analysis of the work. This study submits that: African women were not passive subjects on issues of their reproductive life but agents that could reject imposed values and stick to their tested practices. The ideological and cultural arrogance that characterized the introduction of Western biomedicine had the unintended impact of galvanizing an unexpected resilience of traditional medical practices. Consequently appreciable change in favor of Western biomedicine was only witnessed in the period after independence.